Beware of the Caterpillar: Anaphylaxis to the Spotted Tussock Moth Caterpillar, Lophocampa Maculata. Issue 2 (June 2014) - DuGar, Brandon; Sterbank, Julie; Tcheurekdjian, Haig; Hostoffer, Robert
We present a case report of a 5-year-old boy with presumed anaphylaxis to the caterpillar, Lophocampa maculata, manifesting as the acute development of diffuse urticaria and progressive dyspnea. This reaction required prompt treatment with antihistamines and a bronchodilator. Allergen scratch testing with a homogenized caterpillar extract suggests that immunoglobulin E–mediated type I hypersensitivity as the pathophysiological mechanism responsible for the boy's anaphylaxis. This case report represents the first documented occurrence of an anaphylactic reaction to Lophocampa maculata and adds to the rare incidence of documented hypersensitivity to the order Lepidoptera.